Analisa Pengaruh LPS, ROE, Likuiditas, Leverage, Ukuran Perusahaan, Total Assets Turnover, Kebijakan Pembayaran Dividen Tahun Sebelumnya dan Growth Opportunity Terhadap Kebijakan Pembayaran Dividen pada Perusahaan Properti, Real Estate dan Konstruksi - Franciskus Adriawan (Universitas Tarumanagara, 2020)
The purpose of this study is to examine the influence of earning per share, return on equity, liquidity, leverage, company size, total assets turnover, previous year dividend payment policy and growth opportunity toward dividend payment policy on property, real estate and construction company which are listed in Indonesian Stock Exchange during four years continuously from 2014 until 2017. The sample was determined by purposive sampling method and the model are tested using the multiple linear regression method with SPSS IBM 26. The total sample are 79 samples. Based on the result of the study, it was found that return on equity, company size and previous year dividend payment policy are affecting dividend payment policy.